Types and degrees of interpretive resemblance in translation - Rosales Sequeiros, Xosé (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2001)
This articles explores one of the types of interpretive resemblance found in translation, namely, resemblance between concepts. These are cases where the concept encoded involves a resemblance relation between its literal import and the meaning it communicates, i.e. cases in which words do not literally communicate the concepts they encode. It is argued that translations are often carried out not on the basis of the concept encoded in the original text but on the basis of the actual concept communicated. This constitutes one of the sources of discrepancy found between original and target texts. In these cases, the translation encodes not what was encoded originally but (the translator's interpretation of what) the source concept was intended to communicate. There are three ways in which what is communicated by a concept may depart from what it encodes: concept narrowing, concept loosening, and echoic uses of concepts. In addition to discussing these processes in relation to translation, arguments are put forward for the existence of a further resemblance possibility: concept widening.